2010
DOI: 10.1088/0004-637x/724/2/1133
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Morphology of a Coronal Prominence Cavity

Abstract: We present a three-dimensional density model of coronal prominence cavities, and a morphological fit that has been tightly constrained by a uniquely well-observed cavity. Observations were obtained as part of an International Heliophysical Year campaign by instruments from a variety of space-and ground-based observatories, spanning wavelengths from radio to soft X-ray to integrated white light. From these data it is clear that the prominence cavity is the limb manifestation of a longitudinally extended polar-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
97
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 44 publications
(67 reference statements)
0
97
0
Order By: Relevance
“…1, 2 and 3, can be described by physical models, which can reproduce observed properties and explain and predict their evolution. For CMEs with a common three-part structure, the magnetic field is commonly taken to be of the form of a twisted flux rope contained within an interior plasma cavity (e.g., Gibson et al 2010). The core of the structure is typically considered to be filament material that was supported by the magnetic field above the system's photospheric polarity inversion line (PIL) prior to the eruption.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%
“…1, 2 and 3, can be described by physical models, which can reproduce observed properties and explain and predict their evolution. For CMEs with a common three-part structure, the magnetic field is commonly taken to be of the form of a twisted flux rope contained within an interior plasma cavity (e.g., Gibson et al 2010). The core of the structure is typically considered to be filament material that was supported by the magnetic field above the system's photospheric polarity inversion line (PIL) prior to the eruption.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%
“…In a recent paper by Gibson et al (2010), the authors studied the structure, shape, and evolution (mostly due to the solar rotation) in detail of a stable cavity observed by SOHO/EIT in the wavelength filter at 195 Å. They find that, based on a forward modelling approach, the cavity is darker than the surrounding owing to the depletion in density by a factor of about 2.…”
Section: Introductionmentioning
confidence: 99%
“…. Gibson et al (2010) studied the 3D morphology of a cavity using observations at multiple wavelengths, vantage points, and covering multiple days. The cavity was modeled as a tunnel-like structure, with a Gaussian height (Figure 3, left) and elliptical crosssection.…”
Section: Coronal Cavities: Observationsmentioning
confidence: 99%
“…Forland et al (2013) fit ellipses to all the EUV cavities in the survey, and found a strong tendency (93%) for cavity ellipses to be taller than they were wide. Building on the 3D morphology found by Gibson et al (2010), Schmit & Gibson (2011) extracted density of a coronal cavity from multiwavelength observations. The density was found to be approximately 30% depleted at the center of the cavity relative to the surrounding streamer at the same height.…”
Section: Coronal Cavities: Observationsmentioning
confidence: 99%